Negative associations between general self-efficacy and anxiety/depression among newly HIV-diagnosed men who have sex with men in Beijing, China. Issue 5 (4th May 2019) - Wang, Na; Wang, Suhua; Qian, Han-Zhu; Ruan, Yuhua; Amico, K. Rivet; Vermund, Sten H.; Yin, Lu; Qiu, Xiaoqiang; Zheng, Shimin
ABSTRACT : To evaluate the association between general self-efficacy and depression/anxiety among newly HIV-diagnosed Chinese men who have sex with men (MSM) in Beijing, our study evaluated the baseline survey data of MSM taking part in a clinical trial among Chinese MSM in Beijing. The baseline survey of the trial was conducted between March 2013 and March 2014. General self-efficacy and depression/anxiety were measured using standard scales. Logistic regression and cumulative logistic regression were used to evaluate the associations between general self-efficacy and depression/anxiety. A total of 367 newly HIV-diagnosed Chinese MSM in Beijing were recruited. There were negative associations between general self-efficacy and depression/anxiety among the study population. As general self-efficacy increased by one unit, the odds of "likely" or "borderline" depression versus normal, or "likely" depression versus "borderline" depression or normal decreased by 12% [adjusted odds ratio (AOR): 0.88, 95% confidence interval (CI): 0.85–0.92] after adjusting for potential confounders. Similarly, general self-efficacy was negatively associated with anxiety (AOR: 0.89, 95% CI: 0.86–0.93). A higher level of general self-efficacy was associated with lower levels of depression and anxiety among newly HIV-diagnosed Chinese MSM. Interventions promoting overall health and wellness should address self-efficacy, depression and anxiety.